(untitled) (Interdisciplinary Studies Journal, 2025)
This study aimed to analyze the relationship between sports, leisure, and open socio-educational measures, such as "Community Service and Assisted Freedom," based on interviews with professionals from the "Specialized Reference Centers of Social Assistance" in cities of Campos Gerais, Paraná. Bardin’s "Content Analysis," the approach of Quivy and Campenhoudt, and the "Collective Subject Discourse" by Lefèvre and Lefèvre were used as methodologies. It was identified that sports and leisure play a fundamental role in socio-educational measures. Intersectoriality was highlighted as crucial for overcoming the fragmentation of public policies, enabling collaboration between different sectors. The analysis of the professionals’ responses revealed a social representation regarding the lack of sports and leisure activities, and the difficulty of communication between services (Social Assistance, Health, and Education) as the main challenges. It was noted that sports and leisure are only present in the school environment, and the insufficient practice of intersectoriality was seen as a critical aspect for improving socio-educational measures. It is concluded that well-managed public policies and collaboration between different sectors are essential for promoting social inclusion and the integral development of adolescents in conflict with the law.